2017
DOI: 10.1111/dme.13400
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of biosimilar insulins in Europe

Abstract: Regulatory approval of the first biosimilar insulin in Europe, LY2963016 insulin glargine (Abasaglar®), in 2014 expanded the treatment options available to people with diabetes. As biosimilar insulin products come to market, it is important to recognize that insulin products are biologicals manufactured through complex biotechnology processes, and thus biosimilar insulins cannot be considered identical to their reference products. Strict regulatory guidelines adopted by authorities in Europe, the USA and some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 23 publications
(71 reference statements)
0
44
0
4
Order By: Relevance
“…With the biosimilar Glargin Insulin LY2963016 from Lilly and Boehringer, a first biosimilar insulin has been approved in several countries also for pediatric use and others may be coming soon (ie, biosimilar insulin lispro). In contrast to common generic drugs, insulin molecules are much larger molecules.…”
Section: Biosimilar Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…With the biosimilar Glargin Insulin LY2963016 from Lilly and Boehringer, a first biosimilar insulin has been approved in several countries also for pediatric use and others may be coming soon (ie, biosimilar insulin lispro). In contrast to common generic drugs, insulin molecules are much larger molecules.…”
Section: Biosimilar Insulinmentioning
confidence: 99%
“…Premixed insulins with regular (or rapid acting): NPH in different ratios, for example, 10:90, 15:85, 20:80, 25:75, 30:70, 40:60, 50:50 are available in various countries from different manufacturers. Premixed insulins are suitable for use in pen injector devices.16 | BIOSIMILAR INSULINWith the biosimilar Glargin Insulin LY2963016 from Lilly and Boehringer, a first biosimilar insulin has been approved in several countries also for pediatric use94 and others may be coming soon (ie, biosimilar insulin lispro). In contrast to common generic drugs, insulin molecules are much larger molecules.…”
mentioning
confidence: 99%
“…Once the first reviews, systematic reviews, and metaanalysis about a given topic are published, this can be regarded as a sign of a certain maturity in this area of research. One review reflected mainly on the introduction of BioIns in the EU (15). A U.S. team recently published a systematic review of five different BioIns for which studies have shown no difference between the BioIns and the originator insulins (16).…”
Section: Reviews Systematic Reviews and Meta-analysismentioning
confidence: 99%
“…The widespread availability of generic products has substantially improved access to medicines in low‐ and middle‐income countries . Biosimilar insulins have expanded treatment options for diabetes and can potentially reduce medical costs . LY2963016 insulin glargine, MK‐1293 insulin glargine, Mylan's insulin glargine, and SAR342434 insulin lispro have been approved as biosimilar insulins …”
Section: Introductionmentioning
confidence: 99%
“…Biosimilar insulins have expanded treatment options for diabetes and can potentially reduce medical costs . LY2963016 insulin glargine, MK‐1293 insulin glargine, Mylan's insulin glargine, and SAR342434 insulin lispro have been approved as biosimilar insulins …”
Section: Introductionmentioning
confidence: 99%